REVITALISASI KEMAMPUAN REFLEKSI MAHASISWA CALON GURU MELALUI PENULISAN JURNAL PERKULIAHAN PPKN - Abdillah, Fauzi (Universitas Pendidikan Indonesia, 2017)
Abstract: Reflective Skills of pre-service teacher education students, which when examined in a three-component lens of Civics, namely Civic Knowledge, Skills Civic, and Civic dispositions which would have a very close relationship, there is demonstrated by evidence that encouraging, even to the level of the students and even teachers in the field. Thus, efforts to increase the reflective abilities of students does not meet these expectations, need to be implemented and measured scientifically. With the aim of seeing the process, the response and the effect of the use of journal writing lectures on Civic and Pancasila Education (PPKn), this research will be done by using a mix methods with exploratory research approach. From the research it can be concluded that there is a development of reflective abilities of students. The response of the students showed enthusiasm and motivated them to develop their understanding and skills as a prospective teacher. The study recommends to utilize Class Journal as well as media and learning strategies of innovation in lectures.Keyword: Reflective, Civic Education, Pre-service Teacher Education StudentsÂ Abstrak: Kemampuan reflektif mahasiswa calon guru, yang bila diteropong dalam lensa tiga komponen PKn, yakni Civic Knowledge, Civic Skills, dan Civic Dispositions yang tentu memiliki keterkaitan sangat erat ini, belum memperlihatkan bukti yang menggembirakan, bahkan untuk level mahasiswa bahkan guru di lapangan. Maka, usaha peningkatan kemampuan reflektif mahasiswa yang belum sesuai harapan tersebut perlu untuk dilaksanakan dan diukur secara ilmiah. Dengan tujuan melihat proses, respon dan pengaruh pemanfaatan penulisan jurnal perkuliahan pada mata kuliah PPKn, penelitian ini akan ditempuh dengan menggunakan pendekatan penelitian campuran tipe exploratory. Dari hasil penelitian maka bisa disimpulkan bahwa terjadi perkembangan kemampuan reflektif mahasiswa. Respon dari mahasiswa memperlihatkan antusiasme dan termotivasinya mereka dalam mengembangkan pemahaman dan keterampilan mereka sebagai seorang calon guru. Penelitian ini merekomendasikan untuk memanfaatkan Jurnal Perkuliahan sebagai media dan strategi pembelajaran sekaligus inovasi dalam perkuliahan.Kata Kunci: Reflektif, PPKn, Mahasiswa Calon Guru